2015
DOI: 10.3126/jpn.v5i9.13779
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac conduction system- A detailed study in 46 cases of sudden death

Abstract: Background: Atherosclerotic coronary artery disease is the modern pandemic and is said to be responsible for a major chunk of sudden cardiac deaths. However, in few cases; especially among the young, conduction system abnormalities were found to be the cause of death with absence of significant coronary lesions. These days, examination of the cardiac conduction system during autopsy has been abandoned as it is said to be a time consuming process. The present study was undertaken to highlight the importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Sinus node artery is an unusually stressed artery, coursing through a comparatively dense collagen sheath, which might render it susceptible to mural disease. 2,9 The present study showed FMD of the SA node artery in 44.11% of cases (15 cases) and FMD of AV node artery (14 cases) in 41.17 % cases. FMD is histologically similar to arterial dysplastic changes seen in renal arteries and in other muscular arteries.…”
Section: Conduction Systemmentioning
confidence: 89%
See 2 more Smart Citations
“…Sinus node artery is an unusually stressed artery, coursing through a comparatively dense collagen sheath, which might render it susceptible to mural disease. 2,9 The present study showed FMD of the SA node artery in 44.11% of cases (15 cases) and FMD of AV node artery (14 cases) in 41.17 % cases. FMD is histologically similar to arterial dysplastic changes seen in renal arteries and in other muscular arteries.…”
Section: Conduction Systemmentioning
confidence: 89%
“…Thin longitudinal sections were given from the upper part and transverse sections were given from the lower part to study the respective areas. 2 The coronary arteries were scrutinized for any atheroma, and if present the gross grading of the narrowing was done ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation